SUBTITUSI PEMANFAATAN LIMBAH ASBES UNTUK PEMBUATAN PAVING BLOCK DITINJAU DARI KUAT TEKAN DAN NILAI EKONOMISNYA - Sujatmiko, Heri (Nusantara Hasana Journal, 2024)
Asbestos waste, which was previously just a dirty, smelly waste product that caused many diseases and polluted the environment, can actually be used to make various types of lightweight construction materials that are useful in human life. This is because apart from being able to be utilized from a technical perspective, processed materials from asbestos waste also have high economic value. This research aims to reduce asbestos waste pollution which pollutes the environment and get the best mixture of asbestos waste for making paving blocks, to find out the compressive strength value of asbestos paving blocks and fine aggregate, by comparing the cost between paving from asbestos waste and normal paving. This research was carried out at the Materials Testing Laboratory, Department of Civil Engineering, University of 17 August 1945 Banyuwangi. The method used in this research is experimental with load simulation as a compressive strength test. The paving block model studied was a paving block with a rectangular shape with test object dimensions of width = 10.5cm, thickness = 6cm and length = 21cm. The results show that normal paving has a slightly higher quality value than the asbestos waste paving blocks studied, but in terms of cost, paving blocks from asbestos waste are cheaper than normal paving blocks.